Photosynthetic efficiency and production of cowpea cultivars under deficit irrigation - de Melo, Alberto Soares; da Silva, Allisson Rafael Ferreira; Dutra, Alexson Filgueiras [UNESP]; Dutra, Wellison Filgueiras; Brito, Marcos Eric Barbosa; Sá, Francisco Vanies da Silva (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2018)
Cowpea is a crop with great economic, social and food importance in semi-arid regions, but its production is drastically reduced by the water deficit in these regions, requiring better management strategies that allow the crop’s production. This study therefore aimed to evaluate the photosynthetic efficiency and production of cowpea cultivars under deficit irrigation replacement levels. The experiment tested three cowpea genotypes (G1 = ‘BRS Aracé’, G2 = ‘BR 17 Gurguéia’ and G3 = ‘BRS Marataoã’) and four irrigation depths (40, 60, 80 and 100% of ETc), resulting in a 3 x 4 factorial scheme, arranged in randomized complete blocks design with four replicates. During the experiment, the gas exchanges, chlorophyll a fluorescence and production of the cowpea genotypes under deficit irrigation were evaluated. Carbon fixation in the photosynthetic metabolism of cowpea plants was reduced by accentuated water deficit, regardless of the genotype. The low stress severity was indicated by the lack of effects on chlorophyll fluorescence, indicating that the reduction in the rate of carbon assimilation was due to the stomatal effects. The irrigation with 80% of ETc can be used in the cultivation of the respective cultivars, but with small losses in the production. Among the genotypes, ‘BRS Marataoã’ stands out with respect to yield, with higher values for weight of pods and green beans.
Eficiência fotossintética e produção de cultivares de feijão-caupi sob irrigação deficitária
Keywords: Gas exchanges; Physiology; Vigna unguiculata; Water replacement